On the class of orthogonalizators of the families of exponents with real frequencies - Gubreev , G. M.; Ignatenko , T. R. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We describe complete minimal families of exponential functions and Riesz bases of exponential functions which admit orthogonalizers of a special type. We obtain a complete description of all orthogonalizers of the class of complete minimal family of exponential functions under consideration and formulate a simple condition which guarantees the uniqueness of the orthogonalizer.